2007
DOI: 10.1016/j.bbamem.2007.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Structural organisation of prolamellar bodies (PLB) isolated from Zea mays. Parallel TEM, SAXS and absorption spectra measurements on samples subjected to freeze–thaw, reduced pH and high-salt perturbation

Abstract: Well-organised PLB gives rise to a X-ray diffraction pattern overlaid by a scattering pattern arising from individual tubules within less well-organised regions of the lattice. TEM and SAXS measurements were used to characterise the structural changes in PLB subjected to perturbation by freeze-thaw, exposure to pH 6.5, or resuspension in high-salt media. Comparison of SAXS patterns measured, before and after structural perturbation allows the separation of the contributions from ordered and disordered PLB. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 19 publications
7
34
0
Order By: Relevance
“…Parallel absorption measurements indicated that these structural changes of PLB are accompanied by a conversion of POR-PChlide 640 and POR-PChlide 650 , the photoconvertible forms of the POR-PChlide complex, to a nonphotoconvertible species with absorption maximum close to 635 nm. This species is closely related, if not identical, to POR-PChlide 635 observed for PLB resuspended in low pH assay medium (Selstam et al 2002(Selstam et al , 2007.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…Parallel absorption measurements indicated that these structural changes of PLB are accompanied by a conversion of POR-PChlide 640 and POR-PChlide 650 , the photoconvertible forms of the POR-PChlide complex, to a nonphotoconvertible species with absorption maximum close to 635 nm. This species is closely related, if not identical, to POR-PChlide 635 observed for PLB resuspended in low pH assay medium (Selstam et al 2002(Selstam et al , 2007.…”
Section: Introductionmentioning
confidence: 51%
“…of the type detailed by Solymosi et al (2004Solymosi et al ( , 2006. In a recent paper it was shown that more general non-specific interactions are strongly influenced by the valence of the salt cation and, to a lesser extent, by the chaotropic properties of the salt anion (Selstam et al 2007). Parallel absorption measurements indicated that these structural changes of PLB are accompanied by a conversion of POR-PChlide 640 and POR-PChlide 650 , the photoconvertible forms of the POR-PChlide complex, to a nonphotoconvertible species with absorption maximum close to 635 nm.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For the Q 230 phase based on the gyroid, the two channels are mirror images of each other (one RH and one LH) related by inversion symmetry operations in the space group Ia3d, which are absent from the symmetry group I4 1 32 of the single gyroid. In biological cubic membranes, the two aqueous domains are not necessarily of equal water content, in which case the symmetry group is that of the oriented (single) structures, which exclude operations that interchange the two aqueous domains; this behavior is particularly well-verified for the thylakoid membrane in plant prolamellar bodies, where X-ray scattering experiments clearly give the space groups of the nonoriented (single) version of the bicontinuous diamond membrane (33). The possible asymmetry between the two domains in biological cubic membranes can be rationalized by the possibility that they are connected to different cellular spaces, such as the extracellular, intracellular, or the intrasmooth endoplasmic reticulum (intra-SER) space (10); the asymmetry is also evident in the proposed flow-growth process for the formation of cubic bicontinuous structures by complicated folds of the plasma membrane.…”
Section: Discussionmentioning
confidence: 91%
“…Small-angle x-ray scattering performed on isolated maize (Zea mays) PLBs confirmed their paracrystalline structure, with the diamond cubic lattice being the most abundant type. The unit cell size was 78 nm (Selstam et al, 2007). However, the dimensions of isolated structures and those in sliced tissue, i.e., in situ performed by the ET technique, are difficult to compare.…”
Section: Introductionmentioning
confidence: 99%